Profit Equalization Reserve and Investment Risk Reserve: Issues and its Application - Muchammad Taufiq Affandi (University of Darussalam Gontor, 2019)
The Islamic Financial Institution (IFI) is a unique financial institution which has special characteristics, maqāsid, worldview, risk, and opportunity. One of the methods used to mitigate the unique risk of Islamic banks is the Profit Equalization Reserve (PER) and Investment Risk Reserve (IRR). However, there are some issues related to PER and IRR. Some issues have been identified in the Islamic Financial Services Board (IFSB) guidance note, including profit smoothing and other issues yet to be discussed. This paper tries to observe issues related to PER and IRR and their application in some Islamic banks using content analysis method on their annual reports and/or financial statements. The paper concludes that PER and IRR will bring bigger issues and risks to Islamic banks. This leads the writer to suggest that the regulator reconsider its permissibility. In addition, the paper also finds that the concept of PER and IRR has low acceptance among Islamic banks.